(untitled) (International Journal of Built Environment and Sustainability, 2019)
Brownfield development has become one of the sectors to be emphasised imperatively due to emerging greenfield scarcity throughout Malaysia. A brownfield site may have real or perceived contamination issues that require intervention to revive for beneficial use. As of to-date, there is still a number of brownfield sites in Iskandar Malaysia, albeit brownfield revival projects, via planning and policy measures, have been carried out over the years. In this light, a mode of governance is suggested to be a significant factor in the stagnation and success of brownfield development. Therefore, this paper aims to revisit the urban governance modes of brownfield development in Iskandar Malaysia, with a focus on commercial brownfield development. Specifically, two objectives are highlighted in this paper: (i) to assess the site-level success of completed brownfield developments, namely the Paradigm Mall, Skudai and the Danga City Mall, Johor Bahru; and based on the assessment outcomes, it is then (ii) to identify an efficient and suitable mode of governance for commercial use brownfield development. A measuring tool and an indexing scheme to screen brownfield sites were employed alternately. Results show that the Paradigm Mall achieved a higher site-level success compared to the Danga City Mall. Under this light, compared to the corporatist mode of governance, the clientelistic mode of governance with a material objective is highly in relation to a better success of commercial use brownfield development in the background of Iskandar Malaysia. These findings offer valuable messages and insights to practitioners, particularly local policy-makers, that an often-neglected governance mode approach is essential in determining the brownfield development outcome.